COID-19, Armed Conflict and ICTs Adoption Decisions. Insights from Cameroonian Farmers - Balgah, Roland Azibo; Bwifon, Dorothy Nyiang; Shillie, Peter Ngek (Advances in Social Sciences Research Journal, 2022)
It is common knowledge that adopting information and communication technologies -ICTs can significantly enhance agricultural performance. However, their adoption and usage in African agriculture remains disappointing. This study assesses ICTs adoption rates and adoption determinants among Cameroonian farmers. A structured questionnaire was used to collect data from a random sample of 120 farmers in two selected sites highly hit by COVID 19 and an on-going armed conflict in Cameroon’s North West region. Data collected and analysed using SPSS, version 25.0 revealed an overall ICTs adoption rate of 87.5%: 3 times higher than the national average. Experience with ICTs was the lone variable that significantly influenced ICTs adoption at 95% confidence interval (β=0.414, p=0.034). However, the age of the farmer (β=0.122, P=0.073), ICTs usage in last six months (β=-4, 316, p=0.072), farm size (β=1.132, p=0.06), and farmers income (β=-5.22, p=0.072) significantly influenced ICTs adoption only at the 10 percent level. Based on these results we conclude that high ICT adoption rates by farmers in the study is most likely an adaptation strategy to the combined negative lockdown and ghost town effects of COVID 19 and the on-going armed conflict respectively; which create incentives for ICTs adoption. We recommend ICT awareness campaigns, experience-sharing and capacity building as key activities to sustain ICT adoption and eventually stem future dis-adoption rates. Research thrust on the positive impacts of perceived negative events like COVID 19 and armed conflicts especially in Africa is encouraged.